Exploration of the Path of Green and Low-carbon Development in Counties in Northern Anhui under the Dual Carbon Target - Pu, Mengmeng (International Journal of Global Economics and Management, 2025)
Green water and green mountains are gold and silver mountains. The 20th National Congress of the Communist Party of China proposed to accelerate the transformation of social green development and promote green, low-carbon and high-quality development. Realizing regional green development is an important connotation of high-quality economic development. County towns are key nodes for urban-rural integrated development and important carriers for promoting urban-rural green development. The "dual carbon" target is a necessary choice for my country to promote high-quality development. This project first sorts out the research results of green and low-carbon construction and development in counties at home and abroad, systematically analyzes the basic theories of green and low-carbon, and summarizes the basic characteristics of green and low-carbon development in counties; secondly, an indicator system is established to measure and evaluate the level of green and low-carbon construction and development in counties in northern Anhui, classifies the resource endowments and development levels of different counties from multiple perspectives, and studies the characteristics of green and low-carbon development construction in counties and towns under different types.